Bed behavioral assessment of tomato varieties in Cote d Ivoire - N'ZI, Jean-Claude; FONDIO, Lassina; N’GBESSO, Mako Francois De Paul; DJIDJI, Andé Hortense; KOUAME, Christophe (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Thirty accessions of tomato including twenty eight introduced accessions from The World Vegetable Center-AVRDC and as controls, two commercial varieties Mongal and Calinago, were assessed for agronomic performances at the Experimentation and Production Station of Angud dou of the National Agronomic Research Centre (CNRA) located in the South of Cote d Ivoire. The trial was arranged in a randomized block with three replications. The following parameters were determined at vegetative development stage: plant height at flowering stage, susceptibility of accessions to diseases, day to 50% flowering and day of first harvest, production duration, fruit length, fruit diameter, total number of fruits, number of fruits per plant, potential yield, net yield and fruit damage rate. Results showed that the commercial variety Mongal, with a potential yield of 15.9 and a net yield of 13.1 t ha-1, was the most productive. All the introduced accessions from AVRDC recorded the lowest potential yields from 2.2 to 9.7 t ha-1, and net yields from 1.7 to 8.6 t ha-1. In addition, accessions WVCT8, FMTT847 and WVCT13 were severely infested by bacterial wilt. The reduction of the net yield of tomato accessions resulted in the high fruit damage rates. For the future tomato breeding work, it would be appropriate to introduce into the trials bacterial diseases tolerant varieties. Moreover, some studies could be undertaken to determine the nature of the bacteria involved in the plant wilting and to find out the causal agent of the tomato plants burning at the fructification stage reducing the harvest duration.